1977
DOI: 10.1084/jem.145.5.1101
|View full text |Cite
|
Sign up to set email alerts
|

Hapten-specific delayed hypersensitivity to epsilon-2,4-dinitrophenyl-L-lysine-Ficoll in guinea pigs immunized with 2,4-dinitrophenyl-keyhole limpet hemocyanin.

Abstract: Delayed skin hypersensitivity in guinea pigs was first described by Koch (1) who noted that an extract of tubercle bacilli could induce a prolonged skin reaction when appropriately inoculated into animals which had been made allergic to mycobacteria. Subsequently, Chase (2) showed that the tuberculindelayed type of allergy could be transferred by giving leukocytes derived from immunized animals to otherwise untreated recipients. More recently, Benacerraf and Gell (3-5) and others (6-11) examined the conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In connec tion with the above concept, several types of experi mental inflammation of an allergic nature such as synovitis in rabbits [9][10][11], percutaneous skin reac tions in guinea pigs [12,13] and rats [14,15], footpad reactions in mice [16][17][18], adjuvant arthritis [19][20][21] and type II collagen-induced arthritis in rats [22][23][24] and mice [25] were described in the literature. In those models, however, there are some difficulties in doing quantitative measurements for exudative and prolif erative inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…In connec tion with the above concept, several types of experi mental inflammation of an allergic nature such as synovitis in rabbits [9][10][11], percutaneous skin reac tions in guinea pigs [12,13] and rats [14,15], footpad reactions in mice [16][17][18], adjuvant arthritis [19][20][21] and type II collagen-induced arthritis in rats [22][23][24] and mice [25] were described in the literature. In those models, however, there are some difficulties in doing quantitative measurements for exudative and prolif erative inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been little work on the immune response to DNP-Ficoll in the guinea pig. McMasteret al [12] im munized guinea pigs with DNP-KLH, a T-dependent antigen, in FCA and skin tested them with varying doses of DNP-Ficoll. They found that, DNP-Ficoll el icited both an immediate and delayed-type skin reac tion, which was dependent on the epitope density of the conjugate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, responses of the animals in control groups to immunization with BSA or DNP-KLH were used to eval uate the quality of the animals used in the experiments according to the base information that has been accumulated in our laboratories over a number of years on animal responses to BSA and DNP-KLH antigens with and without adjuvant. BSA and KLH were pur chased from Calbiochem-Behring, La Jolla, Calif. KLH was cou pled to DNP as described previously [17]. The DNP-KLH prepara tion was determined to have 6-9 dinitro-phenyl groups per 50,000 dalton subunit.…”
Section: Preparation O F Antigensmentioning
confidence: 99%